2016
DOI: 10.1175/mwr-d-16-0104.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Unresolved Clouds on Short-Range Global Horizontal Irradiance Predictability

Abstract: The shortwave radiative impacts of unresolved cumulus clouds are investigated using 6-h ensemble simulations performed with the WRF-Solar Model and high-quality observations over the contiguous United States for a 1-yr period. The ensembles use the stochastic kinetic energy backscatter scheme (SKEBS) to account for implicit model uncertainty. Results indicate that parameterizing the radiative effects of both deep and shallow cumulus clouds is necessary to largely reduce (55%) a systematic overprediction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Similarly, WRF-Solar simulations in 2017 in Kuwait produced RMSEs in GHI and DNI of 101Wm −2 and 137 Wm −2 , respectively [44]. Despite regional weather events dominating error statistics, results from WRF-Solar simulations in other countries show the consensus on misrepresentation of clouds and aerosols has not been fully resolved, but has improved from native WRF simulations [36][37][38]41,[43][44][45].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, WRF-Solar simulations in 2017 in Kuwait produced RMSEs in GHI and DNI of 101Wm −2 and 137 Wm −2 , respectively [44]. Despite regional weather events dominating error statistics, results from WRF-Solar simulations in other countries show the consensus on misrepresentation of clouds and aerosols has not been fully resolved, but has improved from native WRF simulations [36][37][38]41,[43][44][45].…”
Section: Discussionmentioning
confidence: 98%
“…All these changes have been incorporated in a specific augmentation of the advanced research version of the WRF Model [35] designed for solar energy predictions known as WRF-Solar [36]. WRF-Solar has been extensively tested in the USA [36][37][38][39][40][41] and other countries, such as Spain [42], Singapore [43], Kuwait [44], and Saudi Arabia [45]. Most studies have reported significant improvements in solar irradiance predictions under different sky conditions with WRF-Solar in comparison to standard WRF simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, and in relation to the transfer of our results to large-scale model, numerical weather prediction models generally account for the cloud shading effects through a decrease in shortwave radiation (i.e., our DOMAIN case) (Jiménez et al, 2016).…”
Section: Moving Forward In Land-atmosphere Interaction Studiesmentioning
confidence: 94%
“…However, biases are present in the global horizontal irradiance (Jiménez et al, 2016; Fig. 4b therein).…”
Section: Moving Forward In Land-atmosphere Interaction Studiesmentioning
confidence: 99%
“…Regarding models in which turbulence and moist convection are parameterized, i.e. mesoscale models, Jimenez et al (2016a) studied the radiative effects of parameterized shallow convection at 9 km horizontal resolution using the mesoscale Weather and Research Forecasting model -Solar (WRF-Solar) (Skamarock et al, 2008;Jimenez et al, 2016b). They used two mass-flux type shallow convective parameterizations, namely those of Deng et al (2003Deng et al ( , 2014 and Grell and Freitas (2014).…”
Section: Introductionmentioning
confidence: 99%